Voluntary Blood Donation: Perception and Practices among Adult Population of a Semi-Urban Area of Delhi - Priya Arora; Manish Arora; Atul Kotwal (Medsci Publications, 2017)
Background: Safe blood can save lives. Increasing regular voluntary non-remunerated blood donation is an important aspect of meeting the safe blood requirements of the country. Methods: This cross-sectional study was conducted among 200 adults in a semi-urban area of Delhi. A pretested questionnaire was used as the tool for the study. Results: 90% of the participants were aware that blood donation is important for saving lives and most (78%) had a favourable attitude towards blood donation. However, in practice, less than 5% had ever donated blood. Educational level had a significant effect on the knowledge regarding blood donation. Conclusion: Although the awareness about blood donation is quite high but very few people have actually donated blood voluntarily. Motivational interactive sessions at the community level are needed to allay the fears and misconceptions related to blood donation.